A case of familial frontotemporal dementia caused by a progranulin gene mutation - Lauryn Currens; Nigel Harrison; Maria Schmidt; Halima Amjad; Weiyi Mu; Sonja W. Scholz; Jee Bang; Alexander Pantelyat (Clinical Parkinsonism & Related Disorders, 2023)
After Alzheimer’s disease, Frontotemporal dementia (FTD) is the most common cause of early-onset dementia. Several genetic mutations have been identified in familial FTD, with mutations in progranulin (GRN) accounting for approximately 20–25% of familial FTD cases and about 10% of total FTD cases. We report the case of a familial FTD patient with atypical parkinsonism who was found to have GRN frontotemporal dementia (GRN-FTD) with a pathogenic splice site mutation (c.709-2A > G) and notable phenotypic heterogeneity among family members.